Baize-like CeO2 and NiO/CeO2 nanorod catalysts prepared by dealloying for CO oxidation. (16th December 2016) - Zhang, Xiaolong; Li, Kun; Shi, Wenyu; Wei, Caihua; Song, Xiaoping; Yang, Sen; Sun, Zhanbo
Abstract: Baize-like monolithic CeO2 and NiO/CeO2 nanorod catalysts were prepared by combined dealloying and calcination and the catalytic activities were evaluated using CO catalytic oxidation. The CeO2 catalysts were composed of nanorods and exhibited a three-dimensional supporting structure with pores. After introduction of NiO, dispersed NiO nanosheets and nanoparticles were supported on the surface of CeO2 nanorods and they were not well-crystallined due to CeO2 inhibiting the NiO crystallization. The Raman and x-ray photoelectron spectroscopy analyses revealed that the introduction of NiO species into CeO2 generated more coordinate unsaturated Ni atoms, oxygen vacancies, defects and active sites for CO catalytic reactions. The reaction activation energy of NiO/CeO2 nanorod catalyst prepared from the Al83 Ce10 Ni7 precursor alloy was just 31.2 kJ mol −1 and the CO conversion can reach up to 97% at 240 °C, which was superior to that of pure CeO2 and nanoporous NiO. The enhanced catalytic activity of baize-like NiO/CeO2 nanorods can be attributed to the strong synergistic effects between finely dispersed NiO species and surface oxygen vacancies in CeO2 nanorods.